Exploring More Sustainable Offshore Logistics Scenarios Using Shared Resources: A Multi-Stakeholder Perspective - Idriss El-Thalji (Logistics)
Offshore logistics has a substantial economic impact in the regions where offshore activities are prevalent, and has a huge opportunity to utilize the shared and collaborative logistics approach. The collaborative and shared logistics approach usually has economic, social, and environmental impacts on several stakeholders within the entire business model. Therefore, the purpose of this paper is to explore and compare the benefits and implications of both separate and shared logistics approaches, from multi-stakeholder perspectives. A case asset is purposefully selected where two offshore installations are located near each other, and have the potential to collaborate and share logistics resources. Three scenarios are studied using a simulation modelling approach: (1) separate logistics vessels, (2) on-demand shared logistics vessels, and (3) scheduled shared logistics vessels. The simulated results show that the shared logistics concept, in this specific case, led to an enhancement in the delivery frequency, number of deliveries, and CO2 emissions. In addition, it provides options either to enhance vessel utilization or create revenue-generating time intervals. The scheduled shared logistics scenario is more sustainable and has a higher probability of being accepted by stakeholders, as it is driven by a revenue-generating mindset.